Algerians and their relationship with the Jerusalem Aukaf and their position on the Zionist occupation - hamidi, boubakeur seddik (The Algerian Historical Journal, 2026)
This research paper deals the emotional connection between Algerians and Jerusalem, and the continuous communication between them. I initially expressed it with the term mahghribins, but I focused on the relation of Algerians with the Jerusalem AUKAF and their position on the Zionist occupation, reviewing the emotional and principled connection and defense of Jerusalem since the Crusades to the Zionist occupation. This expresses the spiritual and cultural presence between the people of mahghribins and Jerusalem and the position of the people of the central Maghreb in it (currently Algeria). they even formed a group that had a religious and cultural impact in Palestine. During the French occupation, how did the Algerian people demonstrate their support and moral and material giving to the Palestinian people, despite the limited effort?